Aditivos naturais, idade de castração e níveis de proteína na dieta de bovinos confinados : desempenho animal, características de carcaça e da carne - Velandia Valero, Maribel (2014)
This work is composed by four studies. In the first, the effects of propolis and functional oils with sorghum silage were evaluated on performance, feed intake, digestibility and complete blood count in growing bulls fed ad libitum in feedlot. In the second study, the effects of propolis and functional oils with corn silage were evaluated on performance, feed intake, digestibility and carcass characteristics in finishing bulls fed ad libitum finished in feedlot. In the third study, the effects of propolis and functional oils with corn silage were evaluated on meat quality of crossbred bulls finished in feedlot. In the fourth study effects of castration age, protein level and lysine/methionine ratio were evaluated in the feed on animal performance, carcass and meat quality of Friesian steers intensively reared. In the first three studies were conducted at Department of Animal Science, State University of Maringá and the fourth at Department of Animal Production and Food Science, University of Zaragoza. In the first three studies, thirty bulls were randomly assigned in factorial system to three treatments: the control diet(CON) with silage (sorghum or corn) (41% or 45.5 total DM) and concentrate (crackedcorn, soybean meal, glycerol, limestone and mineral salt); the propolis-supplemen ted group (PRO) fed with 3 g head-1 day-1 in the form of a premix added to the concentrate and the functional oils-supplemented group (FOL) fed with 3 g head-1 day-1 added to the concentrate. The initial and final live weight were similar for bulls from three diets. However, the average daily gain and the feed efficiency were higher for bulls fed with FOL diet in comparison to bulls in CON and PRO diets. The nutrients digestibility,c arcass characteristics, meat quality, lipid oxidation, chemical composition and fatty acid composition and PUFA/SFA and n-6/n-3 ratio on Longissimus muscle were not affected by the addition of propolis or essential oils in the diets. On the other hand, the final live weight, average daily gain, and hot carcass weights were similar among treatments. In the fourth study, sixty four steers were randomly assigned in factorial system to eight treatments: two castration ages (15 days vs. 5 months), two protein levels (13 vs. 15%) and two lys/met ratio (3.0 vs. 3.4). Feeding treatments started when animals were 3 months old and 92.9 kg of live weight. Castration age did not affect any parameter, not even fat percentage or fatty acid composition, except the ratio PUFA/SFA and n-6/n-3 that increased with late castration. Protein level increased the percentage of muscle in the animal, as well as high ratio lys/met.